PENGARUH PBV DAN NPM TERHADAP HARGA SAHAM PERUSAHAAN DEPARTMENT STORE DI BEI - Dixian Bhikuning; Dara Kusumawati; Hera wasiati; Ivan Jaka Perdana (Jurnal Ilmiah Global Education, 2023)
This study's benefits include examining the effects of Net Profit Margin (NPM) and Price to Book Value (PBV) on Stock Price in Department Store companies listed on the Indonesia Stock Exchange between 2012 until 2021. Three Department Store companies that were listed on the Indonesia Stock Exchange between 2012 until 2021 comprise the sample for this quantitative study. The Classic Assumption Test, Multiple Linear Regression Analysis, Correlation Coefficient, Determination Coefficient, and t-Test and F-Test are the data analysis techniques utilized. The t-Test Research's findings had a significance of 0.216 or greater, indicating that the Price Book Value has no bearing on the stock price of the business. The T-Test Research Results revealed a significance level of 0.016 < 0.05, indicating that the company's stock price is influenced by Net Profit Margin. While the F-Test Research Results, which were obtained with a significance of 0.012 < 0.05, demonstrate that the Net Profit Margin and Price to Book Value both have an effect on the stock price of the company simultaneously.